PEMBARUAN PENDIDIKAN ISLAM DALAM KONTEKS PENDIDIKAN NASIONAL - Muh Idris (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
The transformation of education needs a new way of thinking and practice by complete paradigm shift. It needs a systemic paradigm and emphasizes a basic change in other aspect. Vision in Islamic education development refers to educational reformation and modernization. This point of view is based on monotheism concept combining science and technology. The implications of this vision can be described as follows: developing the branch faculty of IAIN in to independent STAIN, opening wider mandate by developing study programs and converting STAIN and IAIN to be UIN. This is a conversion which may lead Islamic education institutions to play important role in developing science and technology, and to be more competitive in the global era. Hence, Islamic institutions will be the center of excellence in education and culture to develop human civilization, and be the centre of relevant workforce provision.